Prevalence and Antimicrobial Susceptibility Pattern of Methicillin-resistant Staphylococcus Aureus [MRSA] Isolates at a Tertiary Care Hospital in Mangalore, South India - Pai, Vidya; Rao, Venkatakrishna I; Rao, Sunil P (Journal of Laboratory Physicians, 2010)
Background/Aim: Methicillin-resistant Staphylococcus aureus (MRSA) is an important cause of nosocomial infections worldwide. The aim of this study was to determine the prevalence of MRSA and their antimicrobial susceptibility pattern in our hospital located in Mangalore, India.Materials and Methods: The bacterial isolates from various clinical specimens of patients admitted in our hospital were cultured as per standard protocol and all isolates of Staphylococcus aureus obtained were included in the study. The isolates were identified by standard methods like catalase test, slide and tube coagulase tests, and growth on Mannitol salt agar (HiMedia Lab, Mumbai). The antimicrobial susceptibility testing was performed by Kirby–Bauer disc diffusion method. The D-test for inducible clindamycin resistance was performed. The isolates were tested for methicillin resistance by using oxacillin disc by disc diffusion method and confirmed by agar screen test (oxacillin 6 μgm/ml). The results were interpreted according to CLSI criteria.Results: During a period of one year, a total of 237 isolates of S. aureus were studied and 69 (29.1%) were found to be methicillin-resistant. MRSA isolates showed greater resistance to multiple drugs than methicillin sensitive Staphylococcus aureus MSSA isolates. Inducible clindamycin resistance was 18.8% in MRSA as against 3.5% in MSSA. About 40–50% of MRSA were resistant to erythromycin, gentamicin, and chloramphenicol, while less than 30% were resistant to ciprofloxacin and amikacin. However, all strains were sensitive to vancomycin.Conclusion: The regular surveillance of hospital-acquired infections of MRSA may be helpful in formulating and monitoring the antibiotic policy. This may also help in preserving antibiotics like vancomycin, only for life-threatening staphylococcal diseases.
Keywords: Antibiotic; MRSA; prevalence